Online monitoring of wire arc additive manufacturing process: A review - Alkahari, Mohd Rizal; Azizul Izham, Emalyn Damyra Idza; Hussein, Nur Izan Syahriah; Maidin, Shajahan; Ramli, Faiz Redza (Taylor & Francis, 2023)
The rise of wire arc additive manufacturing (WAAM) is attributed to the various field applications of additive manufacturing (AM), especially in producing large metal structures. The wire arc additive manufacturing is a process that can produce near-net-shape structures with high deposition rates and relatively lower costs. Due to the nature of the WAAM process, which is based on layer-by-layer fabrication and repeated heating and cooling cycles, surface defects can occur on the deposited layer, such as pores, cracks, oxidation, and geometric deviation. In understanding the factors that can affect the stability and mechanism of the WAAM process, online monitoring systems has been studied by researchers. This paper aims to critically review the different monitoring techniques as well as distinct sensing methods that can be applied in the WAAM process to enhance the quality of the 3D object. In conducting this review paper, the systematic literature review (SLR) method is chosen to enhance a better understanding of the current research works of monitoring systems in the WAAM process. The high heat accumulation and cooling rate process are found to be the most crucial factors that could influence the geometrical accuracy, microstructure, and mechanical properties of the deposited layer